When and how to update systematic reviews: consensus and checklist. (20th July 2016) - Garner, Paul; Hopewell, Sally; Chandler, Jackie; MacLehose, Harriet; Schünemann, Holger J; Akl, Elie A; Beyene, Joseph; Chang, Stephanie; Churchill, Rachel; Dearness, Karin; Guyatt, Gordon; Lefebvre, Carol; et al.
Abstract : Updating of systematic reviews is generally more efficient than starting all over again when new evidence emerges, but to date there has been no clear guidance on how to do this. This guidance helps authors of systematic reviews, commissioners, and editors decide when to update a systematic review, and then how to go about updating the review.